Cross-linked mixed matrix membranes (MMMs) consisting of aminefunctionalized multi-walled carbon nanotubes and P84 polyimide for organic solvent nanofiltration (OSN) with enhanced flux - Mohammad Hossein Davood Abadi Farahani (Elsevier, 2020)
10.1016/j.memsci.2017.11.037